Hematopoietic stem cell transplantation for Wiskott-Aldrich syndrome: an EBMT Inborn Errors Working Party analysis - Albert, Michael H; Slatter, Mary A; Gennery, Andrew R; Güngör, Tayfun; Bakunina, Katerina; Markovitch, Benyamin; Hazelaar, Sheree; Sirait, Tiarlan; Courteille, Virginie; Aiuti, Alessandro; Aleinikova, Olga V; Balashov, Dmitry; et al. (Blood, 2022)
Allogeneic hematopoietic stem cell transplantation (HSCT) is a potentially curative treatment for patients affected by Wiskott-Aldrich syndrome (WAS). Reported HSCT outcomes have improved over time with respect to overall survival, but some studies have identified older age and HSCT from alternative donors as risk factors predicting poorer outcome. We analyzed 197 patients undergoing transplant at European Society for Blood and Marrow Transplantation centers between 2006 and 2017 who received conditioning as recommended by the Inborn Errors Working Party (IEWP): either busulfan (n = 103) or treosulfan (n = 94) combined with fludarabine ± thiotepa. After a median follow-up post-HSCT of 44.9 months, 176 patients were alive, resulting in a 3-year overall survival of 88.7% and chronic graft-versus-host disease (GVHD)-free survival (events include death, graft failure, and severe chronic GVHD) of 81.7%. Overall survival and chronic GVHD-free survival were not significantly affected by conditioning regimen (busulfan- vs treosulfan-based), donor type (matched sibling donor/matched family donor vs matched unrelated donor/mismatched unrelated donor vs mismatched family donor), or period of HSCT (2006-2013 vs 2014-2017). Patients aged <5 years at HSCT had a significantly better overall survival. The overall cumulative incidences of grade III to IV acute GVHD and extensive/moderate/severe chronic GVHD were 6.6% and 2.1%, respectively. Patients receiving treosulfan-based conditioning had a higher incidence of graft failure and mixed donor chimerism and more frequently underwent secondary procedures (second HSCT, unconditioned stem cell boost, donor lymphocyte infusion, or splenectomy). In summary, HSCT for WAS with conditioning regimens currently recommended by IEWP results in excellent survival and low rates of GVHD, regardless of donor or stem cell source, but age ≥5 years remains a risk factor for overall survival.
Keywords: Wiskottův-Aldrichův syndrom; busulfan; dárci tkání; předškolní dítě; výsledek terapie; Tissue Donors; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; příprava pacienta k transplantaci; Treatment Outcome; Transplantation Conditioning; retrospektivní studie; Busulfan; Child, Preschool; nemoc štěpu proti hostiteli; Wiskott-Aldrich Syndrome; Retrospective Studies; Graft vs Host Disease; Humans